2011
DOI: 10.1007/s11103-011-9771-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the plasma membrane proteins and receptor-like kinases associated with secondary vascular differentiation in poplar

Abstract: The constituents of plasma membrane proteins, particularly the integral membrane proteins, are closely associated with the differentiation of plant cells. Secondary vascular differentiation, which gives rise to the increase in plant stem diameter, is the key process by which the volume of the plant body grows. However, little is known about the plasma membrane proteins that specifically function in the vascular differentiation process. Proteomic analysis of the membrane proteins in poplar differentiating secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 69 publications
1
28
0
1
Order By: Relevance
“…PtPIP2;3/PtPIP2;4, PtTIP2;2 and PtTIP4;1 , highly expressed in wood tissue, were more expressed in ray cambial cells as in fusiform cambial cells [48]. Interestingly PtPIP2;3, PtTIP2;2 and PtTIP4;1 proteins were detected in the plasma membrane of differentiating secondary vascular tissue [49].…”
Section: Resultsmentioning
confidence: 94%
“…PtPIP2;3/PtPIP2;4, PtTIP2;2 and PtTIP4;1 , highly expressed in wood tissue, were more expressed in ray cambial cells as in fusiform cambial cells [48]. Interestingly PtPIP2;3, PtTIP2;2 and PtTIP4;1 proteins were detected in the plasma membrane of differentiating secondary vascular tissue [49].…”
Section: Resultsmentioning
confidence: 94%
“…ribosome, proteasome or protein dimer). During secondary vascular development in poplar, the majority of the integral proteins identified were plasma membrane proteins [58]. Some studies have suggested that up-regulation of plasma membrane aquaporins improves the photosynthetic activity and growth of Eucalyptus trees [59].…”
Section: Discussionmentioning
confidence: 99%
“…Band/spot numbers are indicated in column 8. Proteins identified in previous PM, tonoplast, and chloroplast envelope proteomic studies are indicated in column 9 (PM [6,12,19,33,34]), tonoplast [6,13,18,56], chloroplast envelope [15,17]. TMD: transmembrane domain; MW: molecular weight.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the analysis of cellular proteome complement is necessary. Membrane proteomic studies (plasma membrane (PM), tonoplast, chloroplast, and mitochondrial) in general have greatly contributed to the understanding of salt tolerance in many plant species [6,[12][13][14][15][16][17][18][19]. The PM and tonoplast proteomic studies in Arabidopsis and rice have identified important proteins involved in transport, signal transduction, and membrane trafficking, while a recent proteomic study involving the tonoplast from Mesembryanthemum crystallinum revealed a role for glycolytic enzymes in salt tolerance by the interaction of these enzymes with primary H + -pumps [13].…”
Section: Introductionmentioning
confidence: 99%